Proposed new interior design of Philips Lumileds retail centre for Philips (M) Sdn.Bhd. at Studio 99, Lot 54, Jalan Liew Weng Chee, Jalan Yap Kwan Seng, 50450, Kuala Lumpur / Amirah Farhana Abbas - Abbas, Amirah Farhana (2010)
In this days and age, users have grown more mature when it comes to purchasing any product. The issue that I am bringing forward is about how the seller is going to convince the end users to use their product confidently without feeling any hesitation after purchasing them. It is also the way to convince the end users to buy their products when they are so many competitions out there that are promising the same outcome. The problem with retail centre nowadays, they only display what they are selling without further information on explaining about their product such as how to install the product, or what can you do with the product, what to keep in mind should there be any consequences or defect after few years or things related to the products. The plan is to Proposed New Interior Design of Philips Lumileds Retail Centre for Philips (M) Sdn.Bhd. at Studio 99, Lot 54, Jalan Liew Weng Chee, Jalan Yap Kwan Seng, 50450, Kuala Lumpur. It will not be an ordinary retail centre because the idea is to break away from the normal, typical retail design. The method is to give the future user the clear picture on how the product's functions and the results they are getting from certain products from the display technique. Hence, a new approach and technology on display technique will be used in the retail centre. All data and information gathered throughout the process will be used as a design guidelines to come with a design that will satisfy the client, the end-user and the workers. Therefore, a thorough planning on the space and a suitable image and concept must be choose to implement on this project.